CD40 ligation induces macrophage IL-10 and TNF-alpha production: differential use of the PI3K and p42/44 MAPK-pathways. - Foey, A; Feldmann, M; Brennan, F (2001)
Interleukin 10 (IL-10) is an anti-inflammatory cytokine produced in the rheumatoid arthritis (RA) joint by macrophages/monocytes and infiltrating peripheral blood derived lymphocytes. Recent data suggest a role for physical cell-to-cell interactions in the production of IL-10. In this report, we have investigated the signalling mechanisms involved in IL-10 production by peripheral blood-derived macrophages upon interaction with fixed CD40L transfectants. IL-10 and tumour necrosis factor alpha (TNF-alpha) are produced by macrophage colony-stimulating factor (M-CSF)-primed monocytes/macrophages in response to CD40 ligation. The utilization of the inhibitors, wortmannin and LY294002, demonstrated a role for phosphatidylinositol 3-kinase (PI3K) whereas rapamycin demonstrated p70 S6-kinase (p70S6K) involvement in the production of IL-10 by these monocytes. The production of TNF-alpha was enhanced by wortmannin and LY294002, suggesting negative regulation by PI3K; however, it was dependent on p70S6K suggesting a PI3K-independent mechanism of p70S6K activation. One alternative pathway that activates p70S6K independently of PI3K and also differentiates between IL-10 and TNF-alpha is the p42/44 mitogen-activated protein kinase (MAPK), which regulates TNF-alpha production in a PI3K-independent manner. These observations suggest that CD40 ligation induces macrophage IL-10 and TNF-alpha production, the mechanism of which is p70S6K-dependent yet bifurcates at the level of PI3K and p42/44 MAPK.